Polarization of [lambda] ([lambda] [bar]) hyperons along the beam direction in Au+Au collisions at √sNN=200 GeV - Adam, Jaroslav; Deppner, Ingo Martin; Herrmann, Norbert (Physical review letters, 2019)
The Λ (¯Λ) hyperon polarization along the beam direction has been measured in Au+Au collisions at √sNN=200 GeV, for the first time in heavy-ion collisions. The polarization dependence on the hyperons’ emission angle relative to the elliptic flow plane exhibits a second harmonic sine modulation, indicating a quadrupole pattern of the vorticity component along the beam direction, expected due to elliptic flow. The polarization is found to increase in more peripheral collisions, and shows no strong transverse momentum (pT) dependence at pT greater than 1 GeV/c. The magnitude of the signal is about 5 times smaller than those predicted by hydrodynamic and multiphase transport models; the observed phase of the emission angle dependence is also opposite to these model predictions. In contrast, the kinematic vorticity calculations in the blast-wave model tuned to reproduce particle spectra, elliptic flow, and the azimuthal dependence of the Gaussian source radii measured with the Hanbury Brown-Twiss intensity interferometry technique reproduce well the modulation phase measured in the data and capture the centrality and transverse momentum dependence of the polarization signal.